E-COMMERCE, ACCOUNTING INFORMATION SYSTEMS, FINANCIAL LITERACY AND ACCOUNTING KNOWLEDGE: KEY DRIVERS OF MSME SUCCESS IN MALANG CITY - Khalimatus Sa'Diyyah; Yuliati, Yuliati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study aims to analyse the effect of e-commerce, accounting information systems, financial literacy, and accounting knowledge on the efficiency and effectiveness of MSME performance in Malang City. The present study employed a quantitative approach in its research methodology, which entailed the administration of questionnaires to 98 respondents as a means of data collection.. The present study employed data analysis techniques utilizing SPSS software, which is a statistical software program. The results show that the efficiency and effectiveness of MSME performance in Malang City are significantly influenced by the use of e-commerce and the application of accounting information systems. Meanwhile, financial literacy and accounting knowledge do not have a significant impact on MSME performance in terms of efficiency and effectiveness. These findings confirm the importance of digital technology adoption and structured financial information management to support business sustainability and development in this digital era.